Meta-Analysis of Peripheral Blood Apolipoprotein E Levels in Alzheimer’s Disease - Wang, Chong (Public Library of Science, 2014)
BACKGROUND: Peripheral blood Apolipoprotein E (ApoE) levels have been proposed as biomarkers of Alzheimer’s disease (AD), but previous studies on levels of ApoE in blood remain inconsistent. This meta-analysis was designed to re-examine the potential role of peripheral ApoE in AD diagnosis and its potential value as a candidate biomarker. METHODS: We conducted a systematic literature search of MEDLINE, EMBASE, the Cochrane library, and BIOSIS previews for case-control studies measuring ApoE levels in serum or plasma from AD subjects and healthy controls. The pooled weighted mean difference (WMD) and 95% confidence interval (CI) were used to estimate the association between ApoE levels and AD risk. RESULTS: Eight studies with a total of 2250 controls and 1498 AD cases were identified and analyzed. The pooled WMD from a random-effect model of AD participants compared with the healthy controls was −5.59 mg/l (95% CI: [−8.12, −3.06]). The overall pattern in WMD was not varied by characteristics of study, including age, country, assay method, publication year, and sample type. CONCLUSIONS: Our meta-analysis supports a lowered level of blood ApoE in AD patients, and indicates its potential value as an important risk factor for AD. Further investigation employing standardized assay for ApoE measurement are still warranted to uncover the precise role of ApoE in the pathophysiology of AD.